Multipotential properties of eugenol in pharmacology - comprehensive review of current state of knowledge - Tomasz Łoś; Olga Bielawska; Maciej Rogala; Karol Lorenc; Klaudia Jabłońska; Michał Kuc; Kamila Giżewska; Marta Gulbicka (Kazimierz Wielki University, 2023)
Introduction and purpose: Eugenol is a well-known phenolic chemical substance that can be found in clove oil. Due to its multi-potential properties, it arouse more and more interest from scientists. The possibility of using it as a therapeutic substance in many diseases is being sought. The aim of this review is to summarize the latest information on eugenol, explanation its mechanisms of action and to demonstrate the expanding therapeutic potential. Materials and methods: The literature available on PubMed, Google Scholar was reviewed using the words: "eugenol"; "antibacterial"; "antifungal" ;"antiinflammatory" Description of the state of knowledge: Eugenol demonstrates many pharmacological properties, of which the most essential is the ability to inhibit the growth and eradication of many human pathogens. Its wide spectrum of action covers Gram-negative bacteria as well as some Gram-positive bacteria. Eugenol also represents fungicidal properties, and the mechanism of its action is seen in its ability to deform and disrupt the cell membrane of pathogens. After eugenol penetrates  through the cell membrane excessive amounts ROS are formed and next fatty acids that build the cell membrane are modified, which ultimately leads to the lysis of the pathogen cell. Research on eugenol also proves its anti-inflammatory and analgesic properties by blocking cyclooxygenase and lipoxygenase. The effectiveness of eugenol is comparable to non-steroidal anti-inflammatory drugs.  Summary: Based on the promising results of recent research on the properties of eugenol, it can be expected that in the future it will be used in the production of new therapeutic agents. However, it seems reasonable to conduct more large clinical trials evaluating the effectiveness of eugenol before it is introduced as a therapeutic agent.